Graphene quantum dots-gated hollow mesoporous carbon nanoplatform for targeting drug delivery and synergistic chemo-photothermal therapy - Fang J (Dove Medical Press, 2018)
Junfeng Fang, Yanqing Liu, Yiwen Chen, Dimei Ouyang, Guangji Yang, Tao Yu Department of Gynecology, The First People’s Hospital of Yunnan Province, Kunming University of Science and Technology, Kunming, P.R. China Background: Carbon-based drug delivery systems have attracted great interest because of their excellent photothermal conversion capability and high specific surface area for drug loading. Herein, we report a multifunctional nanoplatform based on hyaluronic acid (HA)-modified and graphene quantum dot (GQD)-gated hollow mesoporous carbon nanoparticle (HMCN) for anticancer drug encapsulation and targeted chemo-photothermal therapy of CD44 receptor-overexpressed cancer cells.Methods: In this design, HMCN was not only used as a nanocarrier with high drug loading content to achieve chemotherapy, but also as a near-infrared absorbing agent to realize photothermal therapy. GQDs could not only prevent premature drug release during blood circulation, but also enhance the chemo-photothermal therapeutic efficacy for complete tumor growth suppression. After being modified with HA, the HA-HMCN(DOX)@GQDs could specifically target cancer cells. Results: As expected, the as-prepared HMCN exhibited high doxorubicin (DOX)-loading capacity of 410 mg/g and excellent light-to-heat conversion property. The DOX was released from HA-HMCN(DOX)@GQDs in a near-infrared laser and pH stimuli-responsive manner, which could enhance the therapeutic effect. In vitro cell biological experimental results confirmed that the nanoplatform possesses excellent biocompatibility, specifically target CD44 receptor-overexpressing human cervical carcinoma HeLa cells, and has remarkable synergistic chemo-photothermal killing capacity. The in vivo therapeutic studies in HeLa xenografts also showed negligible toxicity of HA-HMCN@GQDs and complete inhibition of tumor growth of HA-HMCN(DOX) @GQDs with near-infrared irradiation.Conclusion: The excellent therapeutic effects demonstrated in vitro and in vivo suggested the HMCN-based nanoplatform holds potential for efficient dual-responsive targeting drug delivery and synergistic chemo-photothermal therapy. Keywords: hollow mesoporous carbon nanoparticles, graphene quantum dots, CD44 receptor targeting, chemo-photothermal therapy